Application of Fishbone Diagrams in Developing Budget Implementation and Reporting Systems in the Accounting Department, State Polytechnic of Malang - Puspitasari, Erycha; Aang Afandi; Zainal Abdul Haris (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to identify the root of the problems in the accounting information system for budget implementation and reporting at the Accounting Department, State Polytechnic of Malang. This research uses a qualitative method with a Root Cause Analysis approach. Problems that occur in companies are analyzed using a fishbone diagram. The method of collecting data in this research is in-depth interviews. The results of this research explain that some problems occur in the company as budget implementation and reporting procedures are still being done manually. This research provides a solution for the Accounting Department to create a website that can be used to process budget implementation and reporting in real time, which can increase the effectiveness and efficiency of business processes.